Spheres of reason new essays in the philosophy of normativity - Robertson, Simon (Oxford : Oxford University Press, 2009)
This title comprises nine articles on normativity. They make a timely and distinctive contribution to our understanding of how normative thought may or may not be unified across the spheres of actions, belief and feeling.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Normativity (Ethics)